European Portuguese version of the functional disability inventory: translation and cultural adaptation, validity, and reliability in adolescents with chronic spinal pain. Issue 12 (5th June 2021) - Andias, Rosa; Monteiro, Joana; Santos, Beatriz; Silva, Anabela G.
Abstract: Background: Functional disability affects a large percentage of adolescents with chronic pain. The functional disability inventory (FDI) has been widely described in the literature to assess functional disability, with good psychometric properties. Purpose: To translate and adapt the FDI to European Portuguese language and assess the validity, reliability, and measurement error of this version in adolescents with chronic musculoskeletal pain and, specifically, with neck and low back pain. Method: The translation and cross-cultural adaptation of the FDI was conducted according to international guidelines. After that, 1730 adolescents completed the following scales and questionnaires: FDI, Nordic Musculoskeletal Questionnaire, Numeric Pain Rating Scale, Pain Catastrophizing Scale, Depression, Anxiety and Stress Scale, Tampa Scale of Kinesiophobia, and Basic Scale on Insomnia complaints and Quality of Sleep. Sixty-three of these adolescents, with at least one painful body site, completed the questionnaire twice to assess reliability and measurement error. Exploratory factor analysis and hypothesis testing was used to assess construct validity. Results: Cronbach's alpha ranged from 0.81 and 0.88, ICC was 0.86 (95%CI:0.77; 0.92), the SEM and the SDC were 2.50 and 6.93 (total score of 60 points), respectively. Fair to moderate correlations were obtained between FDI and pain intensity ( r s = 0.33 to 0.43), catastrophizing ( r s = 0.41 to 0.44) depression, anxiety, and stress ( r s = 0.48 to 0.53), fear of movement ( r s = 0.32 to 0.42), and sleep impairments ( r s = 0.34 to 0.38). The factor analysis suggested a two-factor solution. Conclusion: The European Portuguese version of the FDI has very good internal consistency, good test–retest reliability, and construct validity when used in a sample of community adolescents with chronic pain. Implications for rehabilitation: One of the most widely instruments used to assess functional disability is the Functional Disability Inventory (FDI), which in its original version has good psychometric properties and is recommended by the Pediatric Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials; However, the FDI has not been translated yet into European Portuguese language and its psychometric properties have not been assessed in adolescents with chronic spinal pain; This study suggests that the European Portuguese version of the FDI has very good internal consistency, good test–retest reliability as well as construct validity when used in a sample of community adolescents with chronic spinal pain; Therefore, these findings suggest the use of the European Portuguese version of the FDI to assess the functional disability in adolescents with chronic spinal pain.